PANCASILA DALAM POLITIK HUKUM INDONESIA - Mutia Evi Kristhy; Alvin Abraham Shallom; Nani Murni Perdamaian Zai (Fakultas Hukum Universitas Katolik Indonesia Atma Jaya, 2023)
Pancasila is the source of all sources of Indonesian law, so the values ​​of Pancasila, which are contained in the precepts of Pancasila, must be the basis for making national policies in the context of national legal politics. By referring to the Pancasila values ​​which are interconnected, related and inseparable from each other, Indonesian national legal politics is expected to be able to lead the Indonesian people to the goals of the Indonesian state as stated in the Preamble to the 1945 Constitution of the Republic of Indonesia. In this paper, discussed how the existence and position of Pancasila as the basis and reference for national legal politics, Indonesian national legal politics, and how it relates to the goals of the Indonesian state. The research method used is juridical-normative with a statute and a conceptual approach. The results of the research show that the position of Pancasila in national legal politics is the basic foundation in making policies that contain nationalistic, democratic, and social justice values.